Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, Capital Intensity Terhadap Tax Avoidance Dengan Kinerja Keuangan Sebagai Variabel Moderasi - Septya Budi, Chairina Risky; Harry Barli (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
This study aims to analyze the effect of institutional ownership, firm size, and capital intensity on tax avoidance with financial performance as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This study employs financial reports as its primary data source. A purposive sampling technique was utilized, selecting 18 energy sector companies out of 83 over a five-year span, yielding a total of 90 data samples. Panel data regression analysis is applied in this research to examine the data. The data were processed with the help of EViews 13 software and Microsoft Excel 2019. The findings indicate that institutional ownership, firm size, and capital intensity collectively influence tax avoidance. The partial analysis reveals that institutional ownership, firm size, and capital intensity individually do not have a significant impact on tax avoidance. The results of the moderation regression analysis show that financial performance is unable to moderate the effect of institutional ownership on tax avoidance, financial performance is unable to moderate the effect of firm size on tax avoidance, and financial performance is unable to moderate the effect of capital intensity on tax avoidance.